Therapeutic potential of arginine deprivation therapy for gliomas: a systematic review of the existing literature - Yuxiao, Chen; Jiachen, Wang; Yanjie, Lan; Shenglan, Li; Yuji, Wang; Wenbin, Li (Frontiers in Pharmacology, 2024)
BACKGROUND: Arginine deprivation therapy (ADT) hinders glioma cells' access to nutrients by reducing peripheral blood arginine, showing great efficacy in various studies, which suggests it as a potentially promising treatment for glioma. The aim of this systematic review was to explore the mechanism of ADT for gliomas, the therapeutic effect based on existing research, and possible combination therapies. METHODS: We performed a systematic literature review of PubMed, ScienceDirect and Web of Science databases according to PRISMA guidelines, searching for articles on the efficacy of ADT in glioma. RESULTS: We identified 17 studies among 786 search results, among which ADT therapy mainly based on Arginine free condition, Arginine Deiminase and Arginase, including three completed clinical trials. ADT therapy has shown promising results in vivo and in vitro, with its safety confirmed in clinical trials. In the early phase of treatment, glioblastoma (GBM) cells develop protective mechanisms of stress and autophagy, which eventually evolve into caspase dependent apoptosis or senescence, respectively. The immunosuppressive microenvironment is also altered by arginine depletion, such as the transformation of microglia into a pro-inflammatory phenotype and the activation of T-cells. Thus, ADT therapy demonstrates glioma-killing effect in the presence of a combination of mechanisms. In combination with various conventional therapies and investigational drugs such as radiotherapy, temozolomide (TMZ), cyclin-dependent kinase inhibitors (CDK) inhibitors and autophagy inducers, ADT therapy has been shown to be more effective. However, the phenomenon of drug resistance due to re-expression of ASS1 rather than stem cell remains to be investigated. CONCLUSION: Despite the paucity of studies in the literature, the available data demonstrate the therapeutic potential of arginine deprivation therapy for glioma and encourage further research, especially the exploration of its combination therapies and the extrapolation of what we know about the effects and mechanisms of ADT from other tumors to glioma.